A RARE CASE OF NEONATAL DIABETES WITH INSULIN GENE (INS) MUTATION: A CASE REPORT - Zhung, Michael Pook Sow; Anand, L Alexis; Idris, Arini Nuran; Giok, Lim Poi (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Neonatal Diabetes (NDM) is a rare condition that affects 1 in every 100,000-500,000 livebirths. Certain individuals with genetic mutations in NDM can be managed with sulfonylurea therapy while for others, insulin remains the mainstay of treatment. We report an infant having NDM with insulin gene (INS) mutation. CASE We report a small for gestational age (SGA) female born at 39 weeks via spontaneous vaginal delivery (SVD) with birth weight of 2 kg. Her parents are non-consanguineous. She presented with fever, respiratory distress, and vomiting at 3 weeks old. She was dehydrated with 11% weight-loss. Blood investigations revealed metabolic acidosis with pH of 6.92, serum bicarbonate of 5.7 with high anion gap of 25 mmol/L, hyperglycaemia with blood sugar level of 66.15 mmol/L, and blood ketone of 2.7 mmol/L. She had concurrent inappropriately low c-peptide of 54 pmol/L (367-1467) and negative insulin autoantibodies. The genetic result showed heterozygous (p.Pro9Arg) variant in INS gene. She was treated with intravenous fluid therapy and insulin infusion. After 1 week of insulin infusion, she was converted to basal-bolus regimen with subcutaneous regular insulin and NPH insulin which was technically challengingdue to difficulty in dilution and marked glycaemic variability. At 2 months old, she was placed on continuous subcutaneous insulin infusion (Medtronic Minimed 780) with continuous glucose monitoring system. The onset of NDM is less than 6 months-old and genetic testing is indicated for patients diagnosed before 9 monthsold. Typical presentations are SGA, dehydration and hyperglycaemia. Bolus subcutaneous insulin is not ideal in NDM because of frequent feeding, limited subcutaneous fat, reduced insulin requirement, and huge fluctuations in glycaemic levels regardless of the type of insulin used. The successful use of insulin pump has been described in NDM. CONCLUSION Genetic mutations in children with NDM are common. Insulin remains the mainstay of therapy in INS-gene mutation. Genetic testing should be done to facilitate management.